Proceedings Abstracts: Dubai Health Research Conference, November 15-17, 2024, Dubai, UAE - Stefan S Du Plessis; Eman Allam; Bakheet Beshtawy; Reem Raeisi; Tom Loney; Dima Abdelmannan; Ibtihal Makki; Hamda H Khansaheb (Dubai Medical Journal)
Overview: The inaugural Dubai Health Research Conference (DHRC) was held from November 15 to 17th, 2024, during which a diverse range of research topics were presented, reflecting the commitment of Dubai Health and the broader UAE to advancing healthcare through innovation and interdisciplinary research. The conference covered a broad spectrum of disciplines including basic biomedical science, translational research, clinical studies, public health, digital health, artificial intelligence in healthcare, surgical innovations, health professions education, quality improvement, and policy development. The objective of the conference was to showcase state-of-the-art research in which members of Dubai Health were actively involved, both locally in Dubai and internationally.